2020
DOI: 10.1002/ecy.3033
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic factors and plant biomass, not plant diversity, strongly shape grassland arthropods under drought conditions

Abstract: 2020. Abiotic factors and plant biomass, not plant diversity, strongly shape grassland arthropods under drought conditions. Ecology 101(6):Abstract. Arthropod abundance and diversity often track plant biomass and diversity at the local scale. However, under altered precipitation regimes and anthropogenic disturbances, plant-arthropod relationships are expected to be increasingly controlled by abiotic, rather than biotic, factors. We used an experimental precipitation gradient combined with human management in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 46 publications
3
47
2
Order By: Relevance
“…Plant biomass may be itself be driven by trophic structure, complicating the assessment of this response (Schmitz, Krivan, & Ovadia, 2004). If robust, reduced CTMs with plant biomass suggest similar changes in trophic structure as biomass accumulates from drought to heavy rainfall years, and from early to mid-season in seasonal grasslands (Prather, Castillioni, Welti, Kaspari, & Souza, 2020).…”
Section: Temperaturementioning
confidence: 99%
“…Plant biomass may be itself be driven by trophic structure, complicating the assessment of this response (Schmitz, Krivan, & Ovadia, 2004). If robust, reduced CTMs with plant biomass suggest similar changes in trophic structure as biomass accumulates from drought to heavy rainfall years, and from early to mid-season in seasonal grasslands (Prather, Castillioni, Welti, Kaspari, & Souza, 2020).…”
Section: Temperaturementioning
confidence: 99%
“…Specifically, groups like ants and beetles were present during year-round but isopods and diplopods were more abundant at the end of the wet season while chilopods were present all the year but during the dry season they migrated vertically and thus were completely absent in the upper litter. On the other hand, Prather et al [27] found that high soil moisture promoted arthropods while high temperature decreased arthropods. Our results show that arthropod abundance and richness follow a seasonal pattern tight to precipitation, and that arthropods tightly linked to litter are able to overcome drought although in such low abundance that does not support upper trophic levels [24].…”
Section: Variations Through Timementioning
confidence: 99%
“…These results suggest that during the dry season, conditions are such that plants drop leaves and belowground arthropods associated to plants represent a shared subgroup common to all plant species, while further into the dry season, arthropod abundance and richness are at the lowest such that only arthropods specific to plant species are present. Abundance and richness are not linearly related, nevertheless an increase in abundance results in more species, for example Prather et al [27] found that for every 16 individuals a new species appears. From these data we can expect that a decrease in abundance results in loss of species, therefore, in our study the decrease in abundance at the beginning of the dry season may have resulted in a decrease in species such that only stress-tolerant arthropod species [27] were present in all plant species producing a homogenization of the arthropod community.…”
Section: Variations Through Timementioning
confidence: 99%
See 2 more Smart Citations